Privatization under Mrs. Thatcher: a review of the literarture - Marsh, David
According to the author, Public Administration not only publishes original articles but it also seeks to provide material which will be useful to teachers and students alike. In order to strengthen this facet of the journal, the editors are introducing an occasional series of articles which will review the current state of the literature in the various sub-fields within the subject of Public Administration. The contribution by David Marsh reviews the `state of the art' on privatization in Britain. The objective is to draw together the extensive literature in a systematic fashion by identifying key texts and the main research findings. His review examines the origins of privatization, the several meanings of
Keywords: Thatcher, Margaret; Privatisation - U.K; Government Enterprise, Sale of - U.K